Brief Report: Is Cognitive Rehabilitation Needed in Verbal Adults with Autism? Insights from Initial Enrollment in a Trial of Cognitive Enhancement Therapy. - Eack, Shaun; Bahorik, Amber; Hogarty, Susan; Greenwald, Deborah; Litschge, Maralee; Mazefsky, Carla; Minshew, Nancy (Journal of Autism & Developmental Disorders, 2013)
Cognitive rehabilitation is an emerging set of potentially effective interventions for the treatment of autism spectrum disorder, yet the applicability of these approaches for 'high functioning' adults who have normative levels of intelligence remains unexplored. This study examined the initial cognitive performance characteristics of 40 verbal adults with autism enrolled in a pilot trial of Cognitive Enhancement Therapy to investigate the need for cognitive rehabilitation in this population. Results revealed marked and broad deficits across neurocognitive and social-cognitive domains, despite above-average IQ. Areas of greatest impairment included processing speed, cognitive flexibility, and emotion perception and management. These findings indicate the need for comprehensive interventions designed to enhance cognition among verbal adults with autism who have intact intellectual functioning.